One-year outcomes of fixed treatment of intravitreal aflibercept for exudative age-related macular degeneration and the factor of visual prognosis. Issue 31 (August 2018) - Ono, Aoi; Shiragami, Chieko; Manabe, Saki; Takasago, Yukari; Osaka, Rie; Kobayashi, Mamoru; Yamashita, Ayana; Tsujikawa, Akitaka; Hirooka, Kazuyuki
Abstract : Abstract: The aim of this study was to investigate the efficacy of periodic intravitreal aflibercept (IVA) in exudative age-related macular degeneration, and to explore the predictive factors for visual outcome. This is a prospective interventional case series. Fifty-two eyes of 52 treatment-naïve age-related-macula-degeneration patients were enrolled. All participants received IVA bimonthly following 3 monthly loading dose. The primary endpoint was change in best corrected visual acuity (BCVA) and central retinal thickness (CRT), and the secondary outcomes included changes in subfoveal choroidal thickness (SCT), macular atrophy (MA), and retinal average sensitivity (AS) determined by microperimetry at 12 months compared with baseline. The predictive factors for the change of BCVA were examined. Of 52 enrolled patients, 4 patients were drop out. Remaining 48 patients were examined. Mean logMAR BCVA significantly improved from 0.42 ± 0.37 at baseline to 0.29 ± 0.34 at 12 months ( P  = .008). Mean CRT and SCT significant reduced from 285.6 ± 135.2 μm, 247.9 ± 96.7 μm at baseline to 233.4 ± 98.0 μm, 208.1 ± 94.6 μm at 12 months, respectively ( P  < .001). At 12 months, 35 eyes of 48 eyes (72.3%) were archived dry macula. MA occurred in 7 eyes of 35 eyes with dry macula at 12 months (20.0%). AS was significant improved ( P  = .027) between baseline (median: 15.7 dB) and 12 months (median: 19.5 dB). The BCVA of the cases with MA involved fovea was significant worse. Age was significantly predicted for the BCVA at 12 months. IVA administered over 1 year improved BCVA, AS, and morphological findings, and the predictive factors for BCVA were age and MA-involved fovea.